High IFN-gamma and TNF production by peripheral NK cells of colombian patients with different clinical presentation of Plasmodium falciparum (2012)
ABSTARCT: In Colombia, Plasmodium falciparum infection rarely results in severe disease or mortality compared to infections in African populations. During natural infection NK cells exhibit a cytolytic effect and regulate dendritic cells, macrophages, neutrophils as well as affect antigen specific T and B cell responses. To characterize the NK cells in P. falciparum infected patients of a highly endemic region of Colombia, the degree of NK proliferation and production of IFN gamma and TNF production in these cells were explored. Methods: Seventeen patients with acute and three with severe P. falciparum malaria patients from the Northwest region of the country were recruited in the study. In addition, 20 healthy controls were included: 10 from Medellin (no-transmission area) and 10 from the Uraba region (a malaria endemic area). Immunophenotypic analysis of peripheral mononuclear cells was performed by FACS to detect total number of NK cells, subtypes and intracellular IFNg and TNF production by NK cells in the different patient groups. Results: The total mean CD56+ /CD3- NK cell proportions in acute and severe malaria subjects were 9.14% (7.15% CD56dim, 2.01%CD56bright) and 19.62% (16.05%CD56dim, 3.58%CD56bright), respectively, in contrast to healthy controls from endemic (total mean CD56+/CD3-1.2%) and non-endemic area (total mean CD56+/CD3- 0.67%). Analysis of basal IFNg and TNF levels confirmed the CD56bright NK population as the main cytokine producer (p <0.0001) in the groups affected with malaria, with the CD56dim NK cell exhibiting the highest potential of TNF production after stimulus in the acute malaria group. Conclusions: The results confirm the important role of not only CD56bright but also of CD56dim NK cell populations as producers of the two cytokines in malaria patients in Colombia.